Enhancing Latent Tuberculosis Infection Treatment Adherence with Mobile Health Intervention: A Quasi-Experimental Study - Kumar, Rohitashwa; Singhal, Manmohan; N, Ravishankar; Sinha, Abhijeet P; Verma, Ashwani; Kumar, Bhavna; Islam, KM Monirul (National Journal of Community Medicine, 2024)
Introduction: While detecting active TB is central to public health efforts, modelling indicates that reducing latent TB through preventive therapy is crucial. Current regimens mitigate risk but are lengthy and have side effects, necessitating support for uninterrupted treatment. This paper presents the development and evaluation of a digital health platform designed to enhance adherence among LTBI patients. Methods: A Quasi-experimental study was conducted among LTBI patients in Delhi. A total of 163 participants were allocated to intervention (n=82) and control (n=81) groups. Participants were followed up for 6 months post recruitment. Effectiveness of mobile application was evaluated through quantitative tools. Results: Intervention group participants showed slightly higher treatment completion rates (65.91%), in comparison to participants in control group (63%). The analysis demonstrated no co-relation of gender, age, education and employment with treatment completion rates in intervention group. While text and video-based interventions have shown success, there remains a need for more user-centric digital health interventions in this area, given the limited number of studies to date. Conclusion: The mobile health applications can be useful for LTBI care. However, there is a need of involving users during development so that continued interest of users can be ensured.